Социальное значение асоциальных граффити (Бытование и функции современных киевских граффити) - Головаха, И. (Социология: теория, методы, маркетинг, 2004)
This article examines contemporary Kyiv graffiti in their cultural and social context. The author analyzes their main characteristics and the popularity of certain styles among Ukrainian urban adolescents. Graffiti written on Kiev walls represent the thoughts, attitudes, and values of certain social groups. An understanding of them depends upon the symbolic language of traditional graffiti images around the world, and may serve to improve communication between adults and a new generation.